Karakteristik Pendidik dan Nilai-Nilai Karakter dalam Bait Matan Syatibiyyah - Budi Santosa, Aji; Paramansyah, Arman; Faqihudin (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Education plays a crucial role in uncovering and developing an individual's Education plays a very significant role in uncovering and developing an individual's potential, creating people who are not only intellectually smart but also morally upright. However, the current state of education faces serious challenges related to morals and ethics, both from educators and learners. This research aims to explore the characteristics of educators and the values of character in Bait Matan Syatibiyyah. This study employs a descriptive qualitative approach with content analysis methods to identify the characteristics of educators and the character values contained in Bait Matan Syatibiyyah. The research findings indicate that the characteristics of educators in Bait Matan Syatibiyyah include sincerity, piety, justice, gentleness and compassion, patience, knowledge, honesty, humility, self-evaluation, being a role model, and consistency. The character values emphasized in Bait Matan Syatibiyyah are being religious, honest, tolerant, disciplined, hard-working, creative, independent, democratic, curious, having a national spirit and love for the country, appreciating achievements, being friendly and communicative, peace-loving, fond of reading, environmentally aware, socially aware, and responsible. The characteristics of educators as described in Bait Matan Syatibiyyah have strong relevance to the instillation of character values in students.